A Retrospective Study: Erysipelas and Cellulitis Patients’ Profile - Amalia Rositawati; Sawitri Sawitri (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Erysipelas and cellulitis are acute infectious diseases caused by Streptococcus pyogenes/haemolytic and Staphylococcus aureus, which attack the subcutaneous tissue and superficial areas (dermis and epidermis). In the course of the disease, erysipelas and cellulitis often fall in a serious condition that requires proper handling. Purpose: To determine a general overview as well as predictive factors of the severity of erysipelas and cellulitis condition. Methods: Retrospective study by evaluating medical records of erysipelas and cellulitis patients in Medical Ward of Dermatology, Dr. Soetomo General Hospital Surabaya from the period of 2012-2014. Results: The incidence of new cellulitis patients during 2012-2014 were 29 cases (67.4%) while erysipelas 14 cases (32.6%). Most of chief complaint were the form of swelling, redness, and pain sensation. The most common of prodromal symptoms were febris, precipitating factors largely due to scratching and stab wounds. Most underlying disease of both erysipelas and cellulitis was anemia. Predilection was common in the lower extremities in erysipelas (92.8%) and cellulitis (93.1%). Normal count of leukocytes in patients with erysipelas was 52.9% and 56.25% in patients with cellulitis. Culture examination was perfomed in 33 (76.74%) of the total 43 cases. Ampicillin injection therapy was commonly used in 22 patients (51.1%). Conclusion: The correct management could increase the recovery rate, prevent complication and recurrency of erysipelas and cellulitis. Key words: cellulitis, erysipelas, Streptococcus pyogenes/haemoliticus, Staphylococcus aureus.